Œdème papillaire isolé révélant une sarcoïdose oculaire: Isolated papillary edema revealing ocular sarcoidosis - Roqai, Yasmine Chaoui (Pan Afr Med J, 2019)
Sarcoidosis is a multisystem granulomatous disorders of unknown cause, characterised by the presence of epithelioid granulomas and giant-cell granulomas without caseous necrosis. Ocular sarcoidosis mainly manifests as bilateral anterior granulomatous uveitis. The involvement of the posterior segment in patients with ocular sarcoidosis is rare and manifests as periphlebitis or choroidal invasion. Isolated papillary edema is uncommon; hence the peculiarity of our case study. Posterior involvement is a prognostic indicator of poor outcome, threatening visual acuity. Early management, in close cooperation with pneumologists and based on systemic corticosteroid therapy, improves visual outcome and reduces complications.